The relationship between board leadership structure and earnings management in Asia-Pacific - Yasser, Qaiser Rafique; Al-Mamun, Abdullah (Emerald Group Publishing Ltd, 2016)
Purpose - This study aims to review the growing research area of behavioral corporate governance; it explores the relationship between CEO duality attributes and earning management in the context of Asia-Pacific countries. Over time, the use by boards of chief executive officer (CEO) duality has fluctuated, and the scholarly conceptualizations of the phenomenon have become more complex. Design/methodology/approach - This paper uses panel data from 330 firm years from Australia, Malaysia, The Philippines and Pakistan by taking a sample of three years from 2011 to 2013. Findings - The results of the analysis reveal that the board leadership structure was not associated with firm performance and financial reporting quality. However, female CEOs impacted negatively on firm performance in Malaysia, The Philippines and Pakistan. Further analyses expose that the firm size was negatively related with performance, whereas established firms in Australia had strong reporting quality. However, large boards assured healthier reporting quality in Australia and Malaysia. Practical implications - This paper provides empirical evidence that a unitary leadership pattern has no significant impact on companies in the Asia-Pacific, and it would be of interest to regulatory bodies, business practitioners and academic researchers. Originality/value - This paper contributes to the literature on corporate governance and earnings management by introducing a framework for identifying and analyzing moderating variables that affect the relationship between the leadership structure and a firm's financial reporting quality